Analisis Deret Vokal Dalam Cerpen “Cerita Si Kancil Dan Buaya” - Suci Barkah; Ardhitya Akbhar; Jihan Suni Nurkhaerunisa N (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This study discusses the vocal series as a sequence of elements in a series of sounds. This abstract reviews the concept of vocal series from a theoretical and practical point of view, focusing on the analysis of vocal series in the short story